2013
DOI: 10.1007/s10552-013-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study

Abstract: Background Increasing evidence suggests that oral microbiota play a pivotal role in chronic diseases, in addition to the well-established role in periodontal disease. Moreover, recent studies suggest that oral bacteria may also be involved in carcinogenesis; periodontal disease has been linked several cancers. In this study, we examined whether lifestyle factors have an impact on antibody levels to oral bacteria. Methods Data on demographic characteristics, lifestyle factors, and medical conditions were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In our study we sought to avoid the influence of smoking (within one year) and antibiotic use (within 30 days) by exclusion criteria. A number of studies have reported that smokers and non-smokers differ in the oral microbiota [3335] and other aspects of oral health [36,37]. Differences between smokers and non-smokers have also been noted in studies of the microbiota at other sites [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we sought to avoid the influence of smoking (within one year) and antibiotic use (within 30 days) by exclusion criteria. A number of studies have reported that smokers and non-smokers differ in the oral microbiota [3335] and other aspects of oral health [36,37]. Differences between smokers and non-smokers have also been noted in studies of the microbiota at other sites [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Smokers’ microbiomes have less diversity, higher prevalence of organisms associated with periodontal pathogenesis and lower prevalence of those associated with health (22,55). There is evidence of lower humoral immune response in both current and former smokers compared to never smokers (56). Our finding of increased breast cancer risk associated with periodontal disease among former smokers who had quit in the past 20 years could be an indication that previous exposure to smoking was significant in the carcinogenic process or that the smoking resulted in a change slow to be reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking has been observed to affect the peripheral immune system through various changes, including a decrease in the activity of natural killer cells, increase in white blood cell counts, and a higher susceptibility to infection [25]. In a study which ascertained plasma antibodies to specific oral bacteria in 395 cancer-free participants, current smokers tended to have lower antibody levels to oral bacteria than never smokers [26]. Similarly, in a sample of 8,153 participants from NHANES III, smokers tended to have lower antibody levels to nine specific periodontal bacteria, but had higher titers to Micromonas micros [27].…”
Section: Discussionmentioning
confidence: 99%